Prognostic significance of programmed cell death‐1‐positive cells in follicular lymphoma patients may alter in the rituximab era. (7th March 2013) - Takahashi, Hiroyuki; Tomita, Naoto; Sakata, Seiji; Tsuyama, Naoko; Hashimoto, Chizuko; Ohshima, Rika; Matsuura, Shiro; Ogawa, Koji; Yamamoto, Wataru; Kameda, Yoichi; Enaka, Makiko; Inayama, Yoshiaki; et al.
Abstract Programmed cell death‐1 (PD‐1) is involved in one of the inhibitory pathways of the B7‐cluster of differentiation (CD) 28 family; this pathway is known to be involved in the attenuation of T‐cell responses and promotion of T‐cell tolerance. PD‐1 is known to negatively regulate T‐cell receptor‐mediated proliferation and cytokine production, lead to alternation in the tumor microenvironment. Although several studies have shown that high levels of PD‐1‐positive cells in follicular lymphoma (FL) patients influence their prognosis, those studies included patients treated without rituximab, and the prognostic impact of PD‐1 positivity in the rituximab era (R‐era) has not yet been elucidated. We retrospectively studied 82 patients with FL uniformly treated with standard R‐CHOP therapy at six institutions between 2001 and 2009 (median follow‐up for survivors: 55 months). We also collected and examined biopsy specimens for diagnosis with respect to PD‐1 positivity. The PD‐1 positivity was significantly higher in male patients and patients with high beta‐2 microglobulin (B2M ≥ 3.0) (P = 0.03 and 0.003, respectively). Three‐year progression free survival (PFS) and overall survival (OS) were 60% and 86%, respectively. By univariate analysis, elevated LDH (P = 0.07) worsened PFS. Male gender (P = 0.03), high FLIPI score (P = 0.05), and high B2M levels (P = 0.08) worsened OS. Multivariate analysis detected no significant prognostic factors, including PD‐1 positivity. However, in male subgroup, high levels of PD‐1‐positive cells were found to be a prognostic factor for PFS. Addition of rituximab might have altered the prognostic impact of PD‐1‐positive cells.